2020
DOI: 10.1016/j.jcot.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical quadrilateral plate for acetabulum fractures involving quadrilateral surface: A review

Abstract: this series of patients, the acetabular reconstruction using 'Anatomic quadrilateral plate' has shown encouraging results. Conclusion: For stabilization of acetabular fractures involving quadrilateral surface area and pelvic brim, various new implants have been used. The Anatomic quadrilateral plate due to its anatomical shape, the various options in fracture fixation is best optimized for management of comminuted acetabulum fractures especially in poor quality bones. It has been successful in achieving good o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Second, elderly individuals have more systemic diseases, limiting the duration of the operation. Finally, most acetabular fractures in elderly individuals are comminuted fractures [ 23 ], which cannot be fixed using ordinary plates. Acetabular fractures in elderly individuals are not the same as those in other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Second, elderly individuals have more systemic diseases, limiting the duration of the operation. Finally, most acetabular fractures in elderly individuals are comminuted fractures [ 23 ], which cannot be fixed using ordinary plates. Acetabular fractures in elderly individuals are not the same as those in other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative results were similar with other published studies. 6 , 22 The three patients with poor clinical results might be due to their own severe osteoporosis that hindered the union of bone. The incidence rate of postoperative complications was 17.39% including incision‐related iatrogenic injuries such as lateral femoral cutaneous nerve injury; these complications generally resolved within 1 month, except for heterotopic ossification.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 However, it is difficult for orthopedic surgeons to manage this particular type of injuries due to co‐morbidities associated with age‐related bone quality and osteoporosis resulting in comminuted fractures of QLS. 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, it only provided resistance to the hip not formed desired buttress effect to the QLS, if the gap was existing between the screws and the QLS, the tendency of reduction loss would never disappear. Kistler et al[35] and R.K. Sen et al [21] published their innovation of QLS buttress plates, their plates provided partial buttress and resistant effect to the broken QLS reducing the rate secondary displacement of fractures. Chen et al reported biomechanical comparison of different xation techniques including a special infrapectineal QLS buttress plate, compared with other plates, which not only provided entire buttress and resistant effect to the broken QLS especial the comminuted fractures, but also formed entire frame of the QLS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some scholars invented variant types of internal xations to x acetabular fractures involving the QLS using above access including the reconstruction plates, lag screws and cerclage wires/cables. [15][16][17][18][19][20][21] Nevertheless, the xation protocol is the same except slight differences. Ulf Culemann et al [22] introduced an novel technique for an additional long infra-acetabular screw placement to form "frame" structure consisting of both columns, the ilioinguinal plate and supra-acetabular screw xation, which achieved a rigid xation for acetabular fractures and prevent displacement of fractured segments.…”
Section: Introductionmentioning
confidence: 99%